Comparative Analysis of Voltage Segmentation (0.8Voc) and Sensorless MPPT Algorithms in PV Pump Systems Operating Under Partial Shading Conditions - Atagün, Yunus; Çelikel, Reşat (My University, 2025)
When photovoltaic (PV) irrigation systems operate under partial shading conditions (PSC), traditional methods are insufficient. In addition to modified traditional methods, artificial intelligence and optimization-based smart methods are used to obtain maximum power from PV systems operating under PSC. These methods use one or more of the PV system's current, voltage, and atmospheric environment variables. In this study, a sensorless Maximum Power Point Tracking (MPPT) algorithm was developed. The proposed algorithm uses the values of the current and speed of the Brushless Direct Current Motor(BLDC) which used in the PV irrigation system. The current, voltage and other parameters of the PV system was not used. The proposed algorithm was compared the 0.8Voc method that used panel data. The proposed MPPT algorithm was tested with a simulation study created in the MATLAB/Simulink environment. In the simulation study, four different PSCs were created and the 0.8Voc method was compared with the proposed method. The obtained results are shown graphically. Accordingly, the superiority of the proposed method was observed in all cases except for the PSC2 case. On the other hand, there is a clear superiority in the speed of the 0.8Voc method. The proposed sensorless MPPT technique operated the PV pump system with high efficiency as 99.9% in the case of PSC1, 95% in the case of PSC2, 99.9% in the case of PSC3 and 99.7% in the case of PSC4.
Keywords: BLDC; Partial shading; PV pump; Sensorless MPPT; 0.8Voc